Сто великих библейских персонажей - Рыжов Константин Владиславович (100 великих, 2009)
Экземпляры: ф.15 (2010) / Инвентарный номер: 53384 / Цена: / Сис.шифр: 86.37 / Авт.знак: С 81 / ГРНТИ: 21.15.61 / ББК: 86.37я2